Onomastic Units in Artistic Works - oglu, Ikhtiyorbek Norov Kamoliddin (European Journal of Life Safety and Stability (2660-9630), 2022)
The range and problems of on mastics are wide, the essence of famous horses, the status of language, the origin of names; their place in society, history, destiny, name, and the problem of people. Names meaning famous and related horses have been used for more than two thousand years. The on mastic system of the Uzbek language is a linguistic phenomenon, rich in scope, multifaceted and interconnected.